Holistic classical interpretation in the relationship between satan and false God : Analysis of the rules of interpretation - Agustin, Hanna Jenifer; Ismail, Hidayatullah; S, Mochammad Novendri; Syafii, Syafii (Priviet Social Sciences Journal, 2026)
This research can examine the overall interpretation of classical Islamic interpretation regarding the complex relationship between Satan and false Gods using analysis based on Qawaid Tarjih principles. Classical Islamic interpretation can be known as a deeper understanding of Islam which is used to study the complex interactions between these creatures. Through the application of Qawaid Tarjih, this researcher reveals the principles of Dasara which will guide interpretation and can provide an understanding of the criteria used by scholars to differentiate between Satan and false God. This finding not only highlights the dichotomy between truth and falsehood to show the usefulness of Qawaid Tarjih as a tool of differentiation, for this reason researchers can explore the broader impact of a holistic understanding of the Islamic community's perception of Satan and false gods which provides insight into its impact on everyday life with provides insight into the teachings of the Islamic religion